PENGARUH ETIKA AUDIT DAN FEE AUDIT TERHADAP KUALITAS AUDIT DI KANTOR AKUNTAN PUBLIK (KAP) KOTA PADANG - Gusti Cahyani; Dewi Zulvia (JURNAL PUNDI, 2019)
This study attempts to know how big the influence of ethics audit ( x1 ) and fee audit ( x2 ), simultaneously and partial on the quality of an audit ( y ) in office accountant the public city, using data collection method in the form of a questionnaire about 66 respondents.In the analysis data using the validity, reliabilitas.dan the assumption that the classic normality, multikolinearitas, heteroskedastisitas.The method of analysis used analytics linear regression multiple regression, the determinan, the f, the t, and the r2 by using the tools spss16.0.The result showed, the audit ethics have influence on variables quality program audit fees in the research also has an effect on variables the quality of a partial audit and simultaneous.